ACUTE EFFECT OF FOAM ROLLER, STATIC AND DYNAMIC STRETCHING ON AGILITY, BALANCE AND ANAEROBIC PERFORMANCE OF UNIVERSITY LEVEL TAEKWONDO PLAYERS. - Sarika Chaudhary; Jash Desai (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background and Aim: The warm-up phase consists of low to moderate intensity stretching exercises. Foam rolling has been a newly accepted technique in warm-up phase. A within-subject experimental study was designed to rectify the acute effects of foam roller, static and dynamic stretching on agility, balance and anaerobic performance of taekwondo players.Materials and Methods: Sixteen male athletes of taekwondo sport were tested for balance, agility and anaerobic performance. All participants performed one of the following protocols: a) 3 min jogging followed by 14 min static stretching (SS), b) 3 min jogging followed by 17 min dynamic stretching (DS), c) 3 min jogging followed by 16 min foam rolling (FR), d) 3 min jogging followed by 17 mins of rest for 4 consecutive days. After the protocol participants performance was assessed using the Balance Error Scoring System (BESS), Star Excursion Balance Test (SEBT), Ilinois Agility Test (IAT) and Running Based Anaerobic Sprint Test (RAST).Results: Results of the repeated measure ANOVA revealed that DS (P≤ 0.010) considerably improved dynamic balance and static balance, whereas FR (P≤ 0.006) and DS (P≤ 0.024) significantly improved static balance. Agility and anaerobic performance showed no significant differences between the four protocols.Conclusion: According to the results of the study, DS protocol showed better improvement in static and dynamic balance. Where as FR protocol has also been effective in improving static balance.